Design and fabrication of covalently linked PEGylated nanohybrids of ZnO quantum dots with preserved and tunable fluorescence. (5th October 2017) - Salman, Muhammad Saad; Riaz, Asim; Iqbal, Azhar; Zulfiqar, Sonia; Sarwar, Muhammad Ilyas; Shabbir, Saima
Abstract: Non-toxicity, high photo stability, biocompatibility and long lasting narrow emissions are some prime factors for an efficient biological marker. Unfortunately, commercial dyes and Cd-based fluorescent probes do not have such characteristics. Therefore, an efficient fluorescent probe is extremely desirable. Herein, functionalized ZnO quantum dots (QDs) and their nanohybrids with polyethylene glycol (PEG) were prepared by a room temperature solution growth tactic using 3-isocyanatopropyltriethoxysilane (3-ICPTES) as a coupling agent. Isocyanato functional groups were hosted on the surface of as prepared ZnO QDs by introducing optimized stoichiometric amounts of 3-ICPTES. The ZnO QDs were further bonded covalently to PEG via urethane linkages by the reaction of isocyanato functionalized ZnO QDs and hydroxyl groups from PEG molecules. The fluorescence was tuned from cyan to yellowish color after the functionalization of ZnO QDs with 3-ICPTES. Moreover, PEGylated nanohybrids showed greater water dispensability with photoluminescence preserved for at least six months. The present synthesis and coupling strategy for QDs may open up new ways to achieve biocompatible nanohybrids with higher stability and efficient luminescence for bio-imaging and biomedical applications. Graphical abstract: Highlights: Effective surface capping efficiency of 3-isocyanatopropyltriethoxysilane is confirmed rendering isocyanato-functionalized ZnO quantum dots (QDs). ZnO QDs of varying sizes and tunable luminescence are produced by altering curing temperatures. Polyethylene glycol (PEG) is covalently linked with QDs to achieve dual fluorescence PEGylated nanohybrids. Nanohybrids' fluorescence is preserved for at least 6 months which is appropriate for lasting bio-imaging applications.